Overlap of dengue fever and HELLP syndrome in pregnancy: a complex clinical encounter - Garg, Hanish; Gupta, Kabir; Harsh, F. N. U.; Gohri, Jay; Rathee, Amrita (International Journal of Research in Medical Sciences, 2024)
Dengue fever is an arboviral infection caused by the bite of an infected Aedes mosquito, common in tropical areas, especially in India. It is characterized by fever, fatigue, malaise, joint pain, retrobulbar pain, abdominal pain, and thrombocytopenia. It is often complicated by bleeding manifestations like petechiae, bleeding gums, and blood in vomitus. Hemolysis, elevated liver enzymes, low platelet count (HELLP) syndrome is usually a complication of preeclampsia in pregnancy (elevated blood pressure after 20 weeks of gestation) and is characterized by hemolysis, elevated liver enzymes, and low platelet count. This is the case of a primigravida that presented at 32 weeks + 2 days of gestation with dengue fever in the background of HELLP syndrome. Significant overlap in the features of dengue fever and HELLP syndrome can lead to a delay in the diagnosis of HELLP syndrome and its management. This case highlights the importance of early recognition of HELLP syndrome in a dengue positive pregnant patient.